CP-022 Nationally agreed standards for ward pharmacy services – how are we doing?. (14th February 2016) - Jeffery, L; Fischer, H
Abstract : Background: In our country, a newly formed working group coordinates and develops clinical and ward pharmacy services nationally. In 2014, the group agreed on, produced and implemented, national standards for ward pharmacy services. The 35 standards are classified into two groups: basic elements that must be present when providing the ward pharmacy services (n = 16) and optional elements that can be included if resources are available and the service is requested by the ward (n = 19). The standards cover all aspects of ward pharmacy (eg, logistics, storage, provision of information, patient specific elements and prescription review). Purpose: National benchmarking was carried in October 2014 to investigate to what degree the services were provided by hospitals in our country, and to establish a baseline for ward pharmacy services nationally. Material and methods: An electronic questionnaire was sent to the members of the national working group, representing all public hospitals in the country (n = 24). A questionnaire was completed for each hospital (defined as one or a group of hospitals under one Hospital Directors Board). For each of the 35 standards, the reporter was required to specify whether the standards were carried out on all, many, few or no wards at their hospital. Results: 11 of the 16 basic ward pharmacy elements were met fully by all hospitals in our country. The remaining five elements were carried out on all or nearly all wards (21–23 of the 24 hospitals). There was larger variation with respect to the optional ward pharmacy elements, both geographically and regarding the type of optional element. Four elements, primarily related to activities in and around the ward stockroom, were carried out in over 60% of wards, while the seven patient specific elements were only carried out routinely on a few wards. Conclusion: In 2014, nearly all hospitals in our country carried out the basic ward pharmacy elements on all wards. There was greater variation nationally regarding the optional elements. Some were carried out nearly everywhere, while others were carried out on no or few wards. The varying provision of optional elements at particular hospitals probably reflects a lack of resources or demand, rather than a lack of willingness. No conflict of interest.